Comparison of Four Methods for the in vitro Susceptibility Testing of Dermatophytes - Markantonatou, Anthi-Marina; Samaras, Konstantinos; Zachrou, Evaggelia; Vyzantiadis, Timoleon-Achilleas (Frontiers in Microbiology, 2020)
Objectives: Infections caused by dermatophytes affect a high percentage of the population. Antifungal susceptibility testing (AST) can offer useful information about the susceptibility profiles of the pathogens as well as the concomitant documentation of the appropriate treatment.. However, the slow growth rate of these fungi and their poor sporulation are factors that can delay and affect the performance of the AST. The proposed methods by the CLSI or the EUCAST are both laborious for the everyday routine. There are alternative applications which propose the use of an inoculum, consisting of a conidia-mycelium mixture or even plain mycelia, as well as the use of resazurin in order to facilitate the reading. The aim of this study was to compare these approaches to the EUCAST method and evaluate their performance. Methods: Three alternative methods were compared to the EUCAST proposed methodology for conidia forming moulds. The last was defined as the reference method. The methods under evaluation were a) a fragmented mycelia method, b) the EUCAST method with the addition of resazurin sodium salt solution and c) the fragmented mycelia method with the addition of resazurin sodium salt solution. Twenty-two isolates (8 Trichophyton interdigitale, 8 T. rubrum and 6 Microsporum. canis) were tested against the antifungal agents of griseofulvin, terbinafine, fluconazole and itraconazole. Results: The essential agreement between the methods was calculated in percentages and a statistical analysis of the results was performed. Data evaluation revealed sufficient overall agreement of the methods with the addition of resazurin to the initial “uncoloured” methods (98.9% and 97.5% for the EUCAST and the fragmented mycelia methods respectively). The fragmented mycelia method exhibited a relatively sufficient overall agreement in comparison to the EUCAST method (90%) and not a satisfactory correlation, probably as a result of various issues of standardization. Conclusion: The EUCAST method was found to be the more reliable one, whereas the addition of resazurin sodium salt solution facilitates the reading and provides a reliable and objective evaluation, The fragmented mycelia method could serve as an alternative that should be applied only in cases of poor or no sporulating dermatophytes.